logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XII  >>  Math  >>  Relations and Functions
0 votes

Let \(f,\, g\, and\, h\) be functions from \(R\, to\, R.\) Show that \[ (f . g) oh = (foh) . (goh)\]

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • Given two functions $f:A \to B $ and $g:B \to C$, then composition of $f$ and $g$, $gof:A \to C$ by $ gof (x)=g(f(x))\;for\; all \;x \in A$
We have to prove: L.H.S.: $(f.g) oh =$ R.H.S.: $ (foh ).(goh)$.
Consider L.H.S. $(f.g) oh$,
$\Rightarrow (f.g) oh = (f.g) o (h(x))$
$\Rightarrow (f.g) oh = f(h(x)) \times g(h(x))$
We know that given two functions $f:A \to B $ and $g:B \to C$, then composition of $f$ and $g$, $gof:A \to C$ by $ gof (x)=g(f(x))\;for\; all \;x \in A$
$\Rightarrow f(h(x)) = foh$ and $g(h(x)) = goh$
$\Rightarrow$ L.H.S. $= f(h(x)) \times g(h(x)) = (foh) .(goh)$ = R.H.S.
answered Mar 19, 2013 by balaji.thirumalai
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...